Pemberdayaan Virtual reality Untuk Meningkatkan Literasi Digital Guru SMP Negeri 8 Jakarta - Sanjaya Pinem; Muhamad Rosit; Eko Djuniarto (Jurnal Pengabdian kepada Masyarakat Nusantara, 2022)
The limitations of SMP Negeri 8 Jakarta in providing interactive material on solar system material are the main problems that will be solved in this Community Partnership Program (PKM). Schools in the State Capital should be able to set an example for schools outside the State Capital by involving existing and close resources. It will allow teachers to increase student interest in subjects, especially with the solar system. The structured method was used in this service so that the teachers follow every activity to complete it. The solution achieved is divided into three (3) parts, first strengthening knowledge in digital literacy, then enrichment of information technology knowledge based on virtual learning, and last continuous mentoring in virtual reality and augmented reality in interactive learning. The results obtained in this service are an increase in teachers' understanding of digital literacy. It can be seen from the pre-test and post-test results for solutions one and two from 68 to 81. Another result obtained from this service is the response from the students. Service participants were in a good category, as seen from the questionnaires distributed. The importance of using virtual and augmented reality to increase student involvement in learning the solar system is another goal of this service.